Discharge of debts as a method of resolving insolvency - Minaříková, Petra (2012)
The Bachelor's thesis deals with the discharge of debts of a natural person which is governed by the Act No.182/2006 Coll., on Insolvency and Methods of Resolution (the Insolvency Act) and that came into force on January 1st 2008. The aim of this thesis is to provide a fundamental analysis of this non-eliminative method of resolving insolvency and the underlying issues are illustrated by the rulings of the high courts and the Supreme Court of the Czech Republic. The last chapter is devoted to the collective debt relief of the husband and wife, whose bankruptcy estate belongs to community property; this issue is practically created by the practice of the insolvency courts, because the Insolvency Act does not introduce it.